(untitled) (Bangladesh Journal of Zoology, 2023)
Cutaneous leishmaniasis (CL) is an established disease in Sri Lanka. Present study was designed to investigate the epidemiological features, clinical manifestations and the relationship between CL cases and rainfall in Hambantota district, Sri Lanka from March, 2014 to December, 2015. CL suspected patients who presented to Tangalle and Hambantota hospitals during this period were included in the study. After conducting a clinical examination, a descriptive study was carried out using a questionnaire. Slit-skin smears were taken, stained with Giemsa and examined under a light microscope to identify Leishmania amastigotes. Results showed that the highest CL cases were reported from Tangalle District Secretory Division (DSD) out of 12 DSDs in Hambantota district (P<0.05). Majority of patients were >50 years old. Males were more infected than females. Higher number of CL patients were students (χ2 (10) = 6.41, P=0.781). Most of the patients had single lesion on arms, legs and faces/cheeks. Size of the most lesions was >2mm -<1cm and the duration of the most lesions were <06 months. The common clinical characteristics of lesions were erythematous and dry. Further, findings revealed that the higher number of CL cases were reported in March, May, August, October in 2014 and January to March in 2015 in which the study area had received higher amount of rainfall. Findings of the present study showed that the CL incidences and its distribution within Hambantota district had increased. It is essential to consider CL as a public health problem in Hambantota district. Bangladesh J. Zool. 51(1): 71-85, 2023